Maternal periconceptional occupational pesticide exposure and neural tube defects. Issue 11 (15th August 2014) - Makelarski, Jennifer A.; Romitti, Paul A.; Rocheleau, Carissa M.; Burns, Trudy L.; Stewart, Patricia A.; Waters, Martha A.; Lawson, Christina C.; Bell, Erin M.; Lin, Shao; Shaw, Gary M.; Olney, Richard S.; the National Birth Defects Prevention Study; et al.
<x xml:space="preserve">Abstract</x> Background: Adverse associations between maternal pesticide exposure and neural tube defects (NTDs) have been suggested but not consistently observed. This study used data from the multisite National Birth Defects Prevention Study to examine associations between maternal periconceptional (1 month preconception through 2 months postconception) occupational pesticide exposure and NTDs. Methods: Mothers of 502 NTD cases and 2950 unaffected live‐born control infants with estimated delivery dates from 1997 through 2002 were included. Duration, categorical intensity scores, and categorical frequency scores for pesticide classes (e.g., insecticides) were assigned using a modified, literature‐based job‐exposure matrix and maternal‐reported occupational histories. Adjusted odds ratios (aORs) and 95% confidence intervals were estimated based on fitted multivariable logistic regression models that described associations between maternal periconceptional occupational pesticide exposure and NTDs. The aORs were estimated for pesticide exposure (any [yes/no] and cumulative exposure [intensity × frequency × duration] to any pesticide class, each pesticide class, or combination of pesticide classes) and all NTD cases combined and NTD subtypes. Results: Positive, but marginally significant or nonsignificant, aORs were observed for exposure to insecticides + herbicides for all NTD cases combined and for spina bifida alone. Similarly, positive aORs were observed for any exposure and cumulative exposure to insecticides + herbicides + fungicides and anencephaly alone and encephalocele alone. All other aORs were near unity. Conclusion: Pesticide exposure associations varied by NTD subtype and pesticide class. Several aORs were increased, but not significantly. Future work should continue to examine associations between pesticide classes and NTD subtypes using a detailed occupational pesticide exposure assessment and examine pesticide exposures outside the workplace. Birth Defects Research (Part A) 100:877–886, 2014. © 2014 Wiley Periodicals, Inc.